Digital Marketing and Its Impact on Organizational Attraction: An Analytical Study of the Opinions of a Sample of Administrative Leaders in the Public Telecommunications and Information Technology Company - Hamza Khalaf *, Zaid; Fadous Atheeb, Amer (Journal of Economics and Administrative Sciences, 2024)
The main purpose of this research is to understand the role of digital marketing in the Public Telecommunications and Information Company by exploring its four dimensions (communication channels, social media, digital relations, and digital technologies) in enhancing its organizational attractiveness. The problem of the research, the company is struggling how to cover all consumer needs and preferences, comprehend their behavior, and set specific objectives to improve organizational attraction, whether to increase subscribers or enhance interactions with other companies. Digital marketing requires sustained time and effort for long-term success, which is why this research aims to provide a set of marketing mechanisms to address the problem, potentially through electronic platforms or social media. To achieve objective of the research, the descriptive-analytical approach was used. A questionnaire was the main tool used to collect data and information was distributed to a sample of the company’s middle management leaders (119) in the Public Telecommunications and Information Company. the researchers employed a series of descriptive statistical techniques that included the arithmetic mean, standard deviation, coefficient of variation, and simple regression coefficient by using the statistical program (SPSS. V.26). The results confirmed the significant impact of digital marketing on enhancing the leaders’ ability to increase organizational attractiveness, enabling them to execute their assigned activities and tasks more effectively. Paper type: Research paper.